AN ANALYSIS ON STUDENTS’ WRITING MOTIVATION AT SMKN 1 BANGKINANG - Lestari, Intan Surya; Masrul, Masrul; Rianti, Wida (Universitas PGRI Sumatera Barat, 2022)
Low writing motivation is a result of students' lack of interest in writing, their lack of writing vocabulary, and their inability to develop their ideas into written form. There are two types of student motivations: those that come from within the student, known as intrinsic motivation, and those that come from the outside, known as extrinsic motivation. The purpose of this study is to evaluate the writing motivation of students at SMKN 1 Bangkinang Kota. The sample for this study consisted of 36 students in the tenth grade who were majoring in computer and network engineering, with 19 male and 17 female students making up the total. This study employs a quantitative design because it is a suitable method for gathering statistical information to address research questions. The findings demonstrated that SMKN 1 Bangkinang students in the tenth grade had better intrinsic motivation to study English, particularly writing. This is demonstrated by the average intrinsic motivation score (3.76) which is greater than the average extrinsic motivation score (3.31). In other words, they write because they want to be proficient writers.